2020
DOI: 10.22271/chemi.2020.v8.i4af.10062
|View full text |Cite
|
Sign up to set email alerts
|

Growth, yield and essential oil of coriander (Coriandrum sativum L.) variety ACr-2 as influenced by various nutrient levels and crop geometry

Abstract: A field experiment was carried out Rabi season of 2017-18 at research farm of ICAR-NRCSS, Ajmer, Rajasthan to study the growth, yield and essential oil characterization of coriander variety Ajmer Coriander-2 (ACr-2) as influenced by nutrient levels and crop geometry. The experiment was laid out in Factorial Randomized Block Design with four replications. The experiment was comprises three treatment of each crop geometry and nutrient management. Crop geometry G1 (30 cm x 15 cm), G2 (30 cm x 10 cm) and G3 (30 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
(6 reference statements)
2
4
0
Order By: Relevance
“…The reduced intensity of light at the base of the plant might have hastened elongation of poorer internodes leading to increased height of the plants. The recorded crop behaviour under closer spacing is in solid agreement with the results of Diwan et al (2018) and Lal et al (2020), where they reported that in various crops up to a certain level of population, plants grow fast due to self shading but beyond this, elongation is ceased due to reduced photosynthetic activity.…”
Section: Influence Of Plant Geometry On Vegetative Growth and Seed Yieldsupporting
confidence: 90%
See 1 more Smart Citation
“…The reduced intensity of light at the base of the plant might have hastened elongation of poorer internodes leading to increased height of the plants. The recorded crop behaviour under closer spacing is in solid agreement with the results of Diwan et al (2018) and Lal et al (2020), where they reported that in various crops up to a certain level of population, plants grow fast due to self shading but beyond this, elongation is ceased due to reduced photosynthetic activity.…”
Section: Influence Of Plant Geometry On Vegetative Growth and Seed Yieldsupporting
confidence: 90%
“…The efforts like nutrient management and crop breeding programs are important to get better seed yield due to its higher demand for use in confectionery, perfumery and medicine. Application of nutrients at optimal level and geometry of crop (row to row and plant to plant spacing) are the key factors to improve the seed yield of this important spice crop (Lal et al, 2020) The yield levels can be enhanced with the application of optimum nutritional doses and sowing of the crop at appropriate spacing. Since Ajmer Green Coriander-1 (AGCr-1) is a newly developed variety, it was felt that it is necessary to study the response of this variety to the application of different levels of major nutrients (Nitrogen, phosphorous and potassium) and different plant geometry for vegetative growth, yield attributing characters and seed yield.…”
mentioning
confidence: 99%
“…Despite Ethiopia being a centre of primary diversity for the crop 8 , the attention given so far in research and development was very limited. Moreover, crop production remained low compared to its potential yield, which might be due to the deficiency of essential nutrients including nitrogen and phosphorus 19 . In Ethiopia, farmers have been producing different crops including coriander using the blanket recommendation of urea and DAP fertilizers 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Health benefits of coriander include treatment of swellings, diarrhoea, mouth ulcers, anaemia, digestion, menstrual disorders, small pox, eye care, conjunctivitis, skin disorders, blood sugar disorders, protects and soothes liver etc [7]. Green leaf is having high essential oil with good aroma and flavour [8]. The essential oil content in seeds of coriander is 0.47-0.53 per cent whereas major chemical constituents of essential oil are linalool, linalyl acetate along with other important constituents such as thymol, geraniol, carophyllene and pinene [8].…”
Section: Introductionmentioning
confidence: 99%
“…Green leaf is having high essential oil with good aroma and flavour [8]. The essential oil content in seeds of coriander is 0.47-0.53 per cent whereas major chemical constituents of essential oil are linalool, linalyl acetate along with other important constituents such as thymol, geraniol, carophyllene and pinene [8].…”
Section: Introductionmentioning
confidence: 99%